Study Of Interaktif Recognition Letter and Number For Children With Computer Multimedia - Retno .; Margono .; Bambang Eka Purnama (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2008)
ABSTRACT By using computer, children can play with get many good matter, so can developing potency in a child, good that Ianguage potency, artistic and intellegence of child. In consequence shall be given trainings to child for the development of its ability with things took a fancy to children. Matter which need to be tried with application programs having the character of